A Contextual Data Offloading Service With Privacy Support - Gomes, Francisco; Rocha, Lincoln; Trinta, Fernando (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Mobile and context-aware applications are now a reality thanks to the increased capabilities of mobile devices. In the last twenty years, researchers had proposed several software infrastructures to help the development of context-aware applications. We verified that most of them do not store contextual data history and that few of these infrastructures take into account the privacy of contextual data. This article presents a service named COP (Contextual data Offloading service with Privacy support) to mitigate these problems. Its foundations are: (i) a context model; (ii) a privacy policies; and (iii) a list of synchronization policies. The COP aims at storing and processing the contextual data generated from several mobile devices, using the computational power of the cloud. We have implemented one experiment evaluated the impact of contextual filter processing in the mobile device and the remote environment. In this experiment, we measured the processing time and the energy consumption of COP approach. The analysis detected that the migration of data from mobile device to a remote environment is advantageous.